Corrosion and wear resistant protective patch for a turbine blade and method of making same
Patent Information
- Application Number
- CN202611325005.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]TC11钛合金(Ti-6.5Al-3.5Mo-1.5Zr-0.3Si)较Stellite合金具有更优异的高温稳定性,在高温湿蒸汽环境下,组织均匀且不易偏析,因此成为叶片基材的潜在选择,但TC11钛合金抗液滴冲蚀性能稍显不足,其抵抗Cl-离子腐蚀的能力仍需进一步提升以满足末级叶片长期运行需求
[0020]As can be seen from the above technical solution of the present invention, the preparation method of the corrosion-resistant and wear-resistant protective patch for turbine blades proposed in the present invention ensures the uniformity of subsequent reactions and structures by uniformly attaching nanodiamonds to the surface of titanium alloy pre-alloyed powder. Then, through hot isostatic pressing sintering, a three-dimensional network reinforcement structure formed by in-situ TiC particles encapsulating nanodiamonds (TiC-ND) and uniformly distributed at the grain boundaries is controllably constructed in the titanium alloy matrix. Heat treatment is then used to control the dispersion of some in-situ TiC (TiC-ND) within the network structure, thereby constructing a micro-nano multi-scale reinforcement structure.
Smart Images

Figure CN122918375A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal processing technology, and more specifically to a corrosion-resistant and wear-resistant protective patch for turbine blades and its preparation method. Background Technology
[0002] In response to the vulnerability of blades to condensate erosion and Cl in the medium during deep peak-shaving operation in thermal power plants, the issue is that blades operating at reduced frequency are susceptible to erosion from condensate droplets. - The corrosion problem is a common challenge. Currently, the leading edge of turbine blades is generally protected with traditional Stellite alloy coatings. However, Stellite alloy coatings suffer from high-temperature segregation, which can easily induce thermal cracks under high-temperature operating conditions. Furthermore, their resistance to chloride ions (Cl) is limited. - Corrosion resistance may also face challenges in long-term wet steam environments.
[0003] TC11 titanium alloy (Ti-6.5Al-3.5Mo-1.5Zr-0.3Si) exhibits superior high-temperature stability compared to Stellite alloy. In high-temperature, humid steam environments, its microstructure is uniform and less prone to segregation, making it a potential choice for blade substrates. However, TC11 titanium alloy shows slightly insufficient resistance to droplet erosion, particularly in its resistance to Cl-. - The ability to withstand ion corrosion still needs to be further improved to meet the long-term operating requirements of the last stage blades.
[0004] For turbine last-stage blades operating in wet steam environments, they must simultaneously resist droplet erosion and Cl-. - The requirement for synergistic damage from corrosion currently lacks an effective single-material solution. Summary of the Invention
[0005] The purpose of this invention is to address the shortcomings of existing leading-edge protection blades for steam turbine blades by providing a corrosion-resistant and wear-resistant protective patch for steam turbine blades and its preparation method. The invention employs a hot isostatic pressing (HIP) sintering process, using reinforcing units generated in an in-situ reaction system as a foundation. Through micro-nano multi-scale structure construction, the spatially coordinated arrangement of these units is achieved. Process control ensures sufficient reaction and structural stability, ultimately forming a material system with enhanced comprehensive performance. The prepared steam turbine blade protective patch can significantly improve resistance to chloride ions (Cl). - Ion corrosion resistance and wear resistance.
[0006] According to a first aspect of the present invention, a method for preparing a corrosion-resistant and wear-resistant protective patch for turbine blades is provided, comprising the following steps:
[0007] S1. Weigh the dried nano-diamond powder and titanium alloy pre-alloyed powder according to the required mass percentage, and mix and ball-mill until the nano-diamond powder is uniformly attached to the surface of the titanium alloy pre-alloyed powder to obtain mixed powder.
[0008] S2. The mixed powder obtained in step S1 is sintered using hot isostatic pressing (HIP) sintering process, which allows nanodiamond (ND) to enter the matrix grain boundaries and generate TiC layers in situ, forming a core-shell unit (TiC-ND) with nanodiamond (ND) as the core and TiC as the shell, thus obtaining a rough blank.
[0009] S3. The rough blank obtained in step S2 is subjected to heat treatment to regulate the microstructure, so that a portion of TiC-ND is uniformly distributed at the grain boundaries of the matrix to form a three-dimensional network structure, while another portion of TiC-ND is dispersed within the three-dimensional network structure, thus obtaining the required protective patch.
[0010] As an optional implementation, TiC-ND dispersed within the three-dimensional network structure accounts for 5% to 25% of the total TiC-ND volume.
[0011] As an optional implementation, the size of the nanodiamond powder is 5 nm to 50 nm.
[0012] As an optional implementation, the hot isostatic pressing sintering process includes:
[0013] The mixed powder obtained in step S1 is loaded into a carbon steel sleeve for sealing and degassing, and then placed in a hot isostatic pressing furnace for sintering and heat preservation under vacuum conditions.
[0014] As an optional implementation, the package after powder filling is vacuum-treated to achieve a vacuum level of 1×10⁻⁶ inside the package at a temperature of 500 ℃~600 ℃. -4 pa~1×10 -3 pa.
[0015] As an optional implementation method, the process parameters for hot isostatic pressing sintering include: pressure of 90 MPa to 150 MPa, sintering temperature of 850 ℃ to 920 ℃, and holding time of 4 h to 8 h.
[0016] As an optional implementation method, the process parameters for heat treatment microstructure control include: temperature 1020 ℃~1080 ℃, holding time 1 h~2 h, and air cooling.
[0017] As an optional implementation method, the mass ratio of nanodiamond powder to the mixed powder is 0.5% to 1.5%.
[0018] As an optional implementation, the titanium alloy pre-alloyed powder is TC11 with an average particle size of 53 μm to 150 μm.
[0019] According to a second aspect of the present invention, a turbine blade protective patch prepared by the aforementioned method is provided.
[0020] As can be seen from the above technical solution of the present invention, the preparation method of the corrosion-resistant and wear-resistant protective patch for turbine blades proposed in the present invention ensures the uniformity of subsequent reactions and structures by uniformly attaching nanodiamonds to the surface of titanium alloy pre-alloyed powder. Then, through hot isostatic pressing sintering, a three-dimensional network reinforcement structure formed by in-situ TiC particles encapsulating nanodiamonds (TiC-ND) and uniformly distributed at the grain boundaries is controllably constructed in the titanium alloy matrix. Heat treatment is then used to control the dispersion of some in-situ TiC (TiC-ND) within the network structure, thereby constructing a micro-nano multi-scale reinforcement structure.
[0021] The constructed micro / nano multi-scale reinforcement structure brings about significant performance improvements:
[0022] 1. Improved wear resistance and resistance to droplet erosion: High-hardness nanodiamonds (protected by TiC to prevent graphitization) and in-situ TiC particles are the main wear-resistant phases; the continuous and uniform TiC-ND three-dimensional network structure at the grain boundaries greatly enhances the material's load-bearing capacity and resistance to plastic deformation, effectively resisting droplet erosion and mechanical friction wear; the network structure can effectively hinder crack initiation and propagation, promote crack deflection, improve material toughness, and reduce brittle spalling during wear; the TiC-ND dispersed within the network provides additional pinning and dispersion strengthening effects, further enhancing tribological properties.
[0023] 2. Resistant to Cl - Improved corrosion resistance: On the one hand, the dense, chemically stable TiC-ND three-dimensional network structure is enriched at the matrix grain boundaries, which, combined with increased matrix lattice distortion and dislocation density, increases the concentration of Cl. - Energy migration; on the other hand, hot isostatic pressing (HIP) sintering can effectively ensure the formation of low-porosity, high-density matrices, significantly hindering Cl- - The ion-corrosion medium diffuses into the matrix, while the solid solution of C atoms within the crystal (dispersed in TiC-ND within the crystal) further increases the Cl... - The diffusion barrier of ions, thus, through the synergistic effect of multiple factors, the material's resistance to Cl... - Corrosion resistance is significantly enhanced.
[0024] 3. Controllability of structure: The heat treatment process after hot isostatic pressing can finely control the precipitation morphology and quantity of TiC-ND to balance the volume ratio of TiC-ND to TC11 matrix, thereby balancing the relationship between matrix mechanics and corrosion resistance, and avoiding the decline in mechanical and corrosion resistance due to insufficient or excessive precipitation.
[0025] 4. Excellent comprehensive mechanical properties: The synergistic effect of the three-dimensional network structure reinforcement and dispersion strengthening, combined with the high-density matrix, makes the composite material exhibit excellent performance in terms of hardness and corrosion resistance. Attached Figure Description
[0026] Figure 1 This is a flowchart illustrating the preparation process of the corrosion-resistant and wear-resistant protective patch for turbine blades according to the present invention.
[0027] Figure 2 This is a schematic diagram illustrating the principle of improving corrosion resistance through intracrystalline solid solution of C atoms in this invention.
[0028] Figure 3 These are SEM comparison images of the ball-milled powder from Example 1 of this invention; wherein, Figure 3 Part a in the image is a surface scan of the titanium-based pre-alloyed powder. Figure 3 Part b in the image is a scanning image of the morphology of nanodiamond powder. Figure 3 Part c in the image shows the morphology of the powder after ball milling and mixing. Figure 3 Part d in the diagram is a single-particle morphology image of the powder after ball milling and mixing.
[0029] Figure 4 These are SEM comparison images of samples from embodiments of the present invention; wherein, Figure 4 Part a in the image is a microstructure scan of the ball-milled powder after hot isostatic pressing sintering in Example 1. Figure 4 Part a1 in the image is a tissue scan image after heat treatment regulation in Example 1; Figure 4 Part b in the image is a microstructure scan of the ball-milled powder after hot isostatic pressing sintering in Example 2. Figure 4 Part b1 in the image is a tissue scan image after heat treatment regulation in Example 2; Figure 4 Part c in the image is a microstructure scan of the ball-milled powder after hot isostatic pressing and sintering in Example 3. Figure 4 The c1 portion in the image is a tissue scan image after heat treatment regulation in Example 3; Figure 4 Part d in the image is a microstructure scan of the ball-milled powder after hot isostatic pressing sintering in Example 4. Figure 4 The d1 portion in the image is a tissue scan image after heat treatment regulation in Example 4.
[0030] Figure 5 These are SEM comparison images of the comparative samples of this invention; wherein, Figure 5 Part a in the image is a tissue scan image after heat treatment control in Example 1. Figure 5 Part a1 in the image is an enlarged view of the box within a; Figure 5 Part b in the image is a tissue scan image after heat treatment control in Example 2. Figure 5 Part b1 in the image is an enlarged view of the box in b.
[0031] Figure 6 These are XRD comparison images of samples from embodiments and comparative examples of the present invention.
[0032] Figure 7 This is a comparison chart of the Vickers hardness of samples from the embodiments and comparative examples of this invention.
[0033] Figure 8 This is a comparison chart of corrosion resistance tests on samples from embodiments and comparative examples of the present invention.
[0034] Figure 9 This is a comparison chart of the friction and wear performance tests of the samples in the embodiments and comparative examples of this invention. Detailed Implementation
[0035] To better understand the technical content of the present invention, specific embodiments are described below in conjunction with the accompanying drawings.
[0036] Various aspects of the invention are described in this disclosure with reference to the accompanying drawings, in which numerous illustrative embodiments are shown. The embodiments of this disclosure are not necessarily intended to encompass all aspects of the invention. It should be understood that the various concepts and embodiments described above, as well as those described below in more detail, can be implemented in any of a number of ways.
[0037] Current designs for titanium-based composites mostly focus on improving their mechanical properties, neglecting the impact of the reinforcement itself on corrosion resistance. Although adding too much reinforcement can increase the hardness and modulus of titanium alloys, it will significantly reduce their plasticity and corrosion resistance. Therefore, it is necessary to control the amount and size of the reinforcement to achieve a dual improvement in both mechanical and corrosion resistance.
[0038] Therefore, this invention achieves a significant synergistic improvement in the wear resistance (erosion resistance and abrasion resistance) and Cl⁻ corrosion resistance of titanium alloy protective blades through a combination strategy of "in-situ reaction synergistic enhancement + multi-scale structure construction + process control optimization", perfectly meeting the stringent requirements of turbine blade leading edge for integrated protective patches under deep peak shaving conditions.
[0039] In this invention, in-situ TiC refers to a core-shell unit (TiC-ND) with nanodiamond (ND) as the core and TiC as the shell, and in-situ TiC particles refer to the TiC particle body generated in-situ on the surface of nanodiamond.
[0040] Combination Figure 1 As shown, in a preferred embodiment of the present invention, the method for preparing a corrosion-resistant and wear-resistant protective patch for turbine blades includes the following steps:
[0041] S1. Weigh the dried nano-diamond powder and titanium alloy pre-alloyed powder according to the required mass percentage, and mix and ball-mill until the nano-diamond powder is uniformly attached to the surface of the titanium alloy pre-alloyed powder to obtain mixed powder.
[0042] S2. The mixed powder obtained in step S1 is sintered using hot isostatic pressing (HIP) sintering process, which allows nanodiamond (ND) to enter the matrix grain boundaries and generate TiC layers in situ, forming a core-shell unit (TiC-ND) with nanodiamond (ND) as the core and TiC as the shell, thus obtaining a rough blank.
[0043] S3. The rough blank obtained in step S2 is subjected to heat treatment to regulate the microstructure, so that a portion of TiC-ND is uniformly distributed at the grain boundaries of the matrix to form a three-dimensional network structure, while another portion of TiC-ND is dispersed within the three-dimensional network structure, thus obtaining the required protective patch.
[0044] In an optional example, TiC-NDs dispersed within the three-dimensional network structure account for 5% to 25% of the total TiC-ND volume.
[0045] In an optional example, the size of the nanodiamond powder is 5 nm to 50 nm.
[0046] In an optional example, the hot isostatic pressing (HIP) sintering process includes:
[0047] The mixed powder obtained in step S1 is loaded into a carbon steel sleeve for sealing and degassing, and then placed in a hot isostatic pressing furnace for sintering and heat preservation under vacuum conditions.
[0048] In an optional example, the package after powder filling is vacuum-treated to achieve a vacuum level of 1×10⁻⁶ inside the package at a temperature of 500 ℃~600 ℃. -4 pa~1×10 -3 pa.
[0049] In the optional examples, the process parameters for hot isostatic pressing sintering include: pressure of 90 MPa to 150 MPa, sintering temperature of 850 ℃ to 920 ℃, and holding time of 4 h to 8 h.
[0050] In the optional examples, the process parameters for heat treatment microstructure control include: temperature 1020 ℃~1080 ℃, holding time 1 h~2 h, and air cooling.
[0051] In an optional example, the nanodiamond powder accounts for 0.5% to 1.5% of the mass of the mixed powder.
[0052] In an optional example, the titanium alloy pre-alloyed powder is TC11 with an average particle size of 53 μm to 150 μm.
[0053] The following describes an exemplary method for preparing a metal material suitable for turbine blade protective patches, using TC11 as an example, comprising the following steps:
[0054] (1) Weigh nanodiamond (ND) reinforcing powder and TC11 pre-alloyed powder according to the required mass percentage, dry them in a vacuum environment at 80℃~200℃, and then ball-mill and mix the nanodiamond powder and TC11 pre-alloyed powder.
[0055] The reinforcing powder accounts for 0.5% to 1.5% of the mass of the mixed powder, and the mass ratio of the milling agate ball to the mixed powder is (2 to 5): 1. The milling conditions are: rotation speed 150 r / min to 300 r / min, time 6 h to 12 h.
[0056] (2) The distribution of nanodiamonds on the TC11 pre-alloyed powder particles is observed by SEM after ball milling in step (1). If the reinforcing powder is not uniformly attached to the surface of the titanium alloy pre-alloyed powder, ball milling is continued until the nanodiamond powder is uniformly attached to the surface of the titanium alloy pre-alloyed powder. The final product is TC11-ND mixed powder.
[0057] (3) The TC11-ND mixed powder is loaded into a custom-made package. The package is then vacuum-treated at a temperature of 500℃~600℃ to achieve a vacuum degree of 1×10⁻⁶ inside the package. -4 pa~1×10 -3 After pa, the tube is sealed and degassed and then placed in a hot isostatic pressing sintering furnace. Sintering is carried out under vacuum conditions at a pressure of 90 MPa to 150 MPa. The intermediate holding temperature is 850 ℃ to 920 ℃ and the holding time is 4 h to 8 h. After the holding time is completed, the sintered billet is cooled with the furnace to obtain the sintered billet.
[0058] (4) The sintered blank is subjected to heat treatment control. The heat treatment temperature is 1020 ℃~1080 ℃, the holding time is 1 h~2 h, and the cooling method is air cooling to obtain the required protective patch.
[0059] In another exemplary embodiment of the present invention, a turbine blade protective patch prepared using the aforementioned method is provided.
[0060] Combination Figure 1-2 As shown, the prepared protective patch generates TiC-ND core-shell units through in-situ reaction. This structure not only uses TiC to suppress the high-temperature graphitization of ND to maintain ultra-high hardness, but also combines the high chemical stability of TiC to jointly improve the corrosion resistance of the unit, forming a basic unit with synergistic enhancement of mechanical and corrosion resistance properties.
[0061] By constructing a continuous and uniform three-dimensional network structure of TiC-ND core-shell units at the matrix grain boundaries, ND bears the main load at the mechanical level, while TiC significantly improves the material's resistance to droplet erosion, friction and wear, and load-bearing capacity by inhibiting grain boundary slip and interfacial strengthening, in conjunction with the network structure, and also hinders crack propagation. At the corrosion protection level, the dense and appropriately structured network can effectively block Cl. - It can prevent the penetration of corrosive media, reduce the risk of substrate exposure, and enhance corrosion resistance;
[0062] Some TiC-ND is dispersed within the network structure. Intragranular solid solution enhances the diffusion energy barrier, further improving corrosion resistance. Simultaneously, pinning and dispersion strengthening effects synergistically improve the material's wear resistance, ultimately achieving superior erosion resistance and Cl-resistance. - Improved overall performance in terms of corrosion resistance and mechanical load-bearing capacity.
[0063] Understandably, hot isostatic pressing is a near-net-shape forming process, which can directly produce components of the required shape through hot isostatic pressing sintering.
[0064] To facilitate better understanding, the present invention will be further illustrated below with several specific examples, but the preparation process is not limited to these examples, and the content of the present invention is not limited to these examples.
[0065] Unless otherwise specified, the materials in the examples are prepared according to existing methods or purchased directly from the market.
[0066] For ease of testing, the components sintered in the following examples and comparative examples are cylinders with dimensions of 35 mm in diameter and 120 mm in height (excluding the cladding).
[0067] Example 1
[0068] (1) Powder preparation: Weigh the reinforcing nanodiamond powder and Ti-6.5Al-3.5Mo-1.5Zr-0.3Si powder by mass percentage, dry them in a vacuum environment in an oven, and then mix the powder in a planetary ball mill to obtain a uniformly mixed powder.
[0069] The nanodiamond powder was 0.5 wt.% with an average particle size of 5 nm, and the balance powder was Ti-6.5Al-3.5Mo-1.5Zr-0.3Si powder with a particle size of 53 μm to 150 μm. The drying parameters were 100℃ for 1.5 hours, and the ball milling process was carried out at a mass ratio of 4:1 for agate balls and 200 rpm for 6 hours to obtain the TC11-ND mixed powder.
[0070] (2) The mixed powder from step (1) is placed into a custom carbon steel sleeve for sealing and degassing (degassing at 600 ℃ for 6 hours to achieve a vacuum of 1×10⁻⁶ inside the sleeve). -3 The blank (pa) is placed in a hot isostatic pressing sintering furnace and sintered under vacuum conditions at a pressure of 150 MPa. The intermediate holding temperature is 920 ℃ and the holding time is 4 h. After the holding is completed, the blank is cooled with the furnace to obtain the sintered blank.
[0071] (3) The sintered billet is subjected to heat treatment control. The heat treatment temperature is 1080 ℃, the holding time is 1.5 h, and the cooling method is air cooling.
[0072] Example 2
[0073] (1) Powder preparation: Weigh the reinforcing nanodiamond powder and Ti-6.5Al-3.5Mo-1.5Zr-0.3Si powder by mass percentage, dry them in a vacuum environment in an oven, and then mix the powder in a planetary ball mill to obtain a uniformly mixed powder.
[0074] The nanodiamond powder was 0.75 wt.% with an average particle size of 5 nm, and the balance powder was Ti-6.5Al-3.5Mo-1.5Zr-0.3Si powder with a particle size of 53 μm to 150 μm. The drying parameters were 100 ℃ for 1.5 hours, and the ball milling process was carried out at a mass ratio of 4:1 for agate balls and 200 rpm for 6 hours to obtain the mixed powder of TC11-ND.
[0075] (2) The mixed powder from step (1) is placed into a custom carbon steel sleeve for sealing and degassing (degassing at 600 ℃ for 6 hours to achieve a vacuum of 1×10⁻⁶ inside the sleeve). -3 The blank (pa) is placed in a hot isostatic pressing sintering furnace and sintered under vacuum conditions at a pressure of 150 MPa. The intermediate holding temperature is 920 ℃ and the holding time is 4 h. After the holding is completed, the blank is cooled with the furnace to obtain the sintered blank.
[0076] (3) The sintered billet is subjected to heat treatment control. The heat treatment temperature is 1080 ℃, the holding time is 1.5 h, and the cooling method is air cooling.
[0077] Example 3
[0078] (1) Powder preparation: Weigh the reinforcing nanodiamond powder and Ti-6.5Al-3.5Mo-1.5Zr-0.3Si powder by mass percentage, dry them in a vacuum environment in an oven, and then mix the powder in a planetary ball mill to obtain a uniformly mixed powder.
[0079] The nanodiamond powder accounted for 1.0 wt.% of the total mass, with an average particle size of 5 nm. The remaining powder was Ti-6.5Al-3.5Mo-1.5Zr-0.3Si powder with a particle size of 53 μm to 150 μm. The drying parameters were 100 ℃ for 1.5 hours. The ball milling process was carried out at a mass ratio of 4:1 between agate balls and powder, at 200 rpm for 6 hours to obtain the TC11-ND mixed powder.
[0080] (2) The mixed powder from step (1) is placed into a custom carbon steel sleeve for sealing and degassing (degassing at 600 ℃ for 6 hours to achieve a vacuum of 1×10⁻⁶ inside the sleeve). -3 The blank (pa) is placed in a hot isostatic pressing sintering furnace and sintered under vacuum conditions at a pressure of 150 MPa. The intermediate holding temperature is 920 ℃ and the holding time is 4 h. After the holding is completed, the blank is cooled with the furnace to obtain the sintered blank.
[0081] (3) The sintered billet is subjected to heat treatment control. The heat treatment temperature is 1080 ℃, the holding time is 1.5 h, and the cooling method is air cooling.
[0082] Example 4
[0083] (1) Powder preparation: Weigh the reinforcing nanodiamond powder and Ti-6.5Al-3.5Mo-1.5Zr-0.3Si powder by mass percentage, dry them in a vacuum environment in an oven, and then mix the powder in a planetary ball mill to obtain a uniformly mixed powder.
[0084] The nanodiamond powder accounted for 1.5 wt.% of the total mass, with an average particle size of 5 nm. The remaining powder consisted of Ti-6.5Al-3.5Mo-1.5Zr-0.3Si powder with a particle size of 53 μm to 150 μm. The drying parameters were 100 ℃ for 1.5 hours. The ball milling process was carried out at a mass ratio of 4:1 between agate balls and powder, at 200 rpm for 6 hours to obtain the TC11-ND mixed powder.
[0085] (2) The mixed powder from step (1) is placed into a custom carbon steel sleeve for sealing and degassing (degassing at 600 ℃ for 6 hours to achieve a vacuum of 1×10⁻⁶ inside the sleeve). -3 The blank (pa) is placed in a hot isostatic pressing sintering furnace and sintered under vacuum conditions at a pressure of 150 MPa. The intermediate holding temperature is 920 ℃ and the holding time is 4 h. After the holding is completed, the blank is cooled with the furnace to obtain the sintered blank.
[0086] (3) The sintered billet is subjected to heat treatment control. The heat treatment temperature is 1080 ℃, the holding time is 1.5 h, and the cooling method is air cooling.
[0087] Comparative Example 1
[0088] The difference from Example 1 is that the average particle size of the nanodiamonds is 1 nm.
[0089] Comparative Example 2
[0090] The difference from Example 1 is that the average particle size of the nanodiamonds is 100 nm.
[0091] SEM test
[0092] The powder from Example 1 was subjected to SEM testing, such as... Figure 3 As shown, the nanodiamonds of the present invention are uniformly distributed on the surface of the titanium matrix powder particles.
[0093] SEM tests were performed on the samples after hot isostatic pressing (HIP) and heat treatment in Examples 1-4, as well as the samples after heat treatment. Figure 4 As shown in the figure, it can be seen that in-situ TiC and nanodiamond reinforcement (TiC-ND) form a network reinforcement structure at the grain boundaries to improve the load-bearing capacity of the composite material. After heat treatment, the in-situ TiC (TiC-ND) migrates into the network. A schematic diagram is shown below. Figure 1 As shown, it provides dispersion strengthening, which can effectively improve the mechanical properties of the material.
[0094] like Figure 5 As shown in the SEM images of the heat-treated samples of Comparative Examples 1-2, it can be seen that the addition of ND that is too small (Comparative Example 1) and too large (Comparative Example 2) will affect the microstructure. If it is too small, a network structure cannot be formed during sintering, while if the ND size is too large, the matrix grain boundaries will be coarsened and the network will not contain TiC-ND.
[0095] XRD test
[0096] XRD tests were performed on the mixed powders of Examples 1-4, and the results are as follows: Figure 6 As shown in the figure, besides Ti in the TC11 matrix, the reinforcing phases are TiC and nanodiamond. This indicates that in-situ TiC can stably exist in the composite material, and TiC and nanodiamond produce a synergistic strengthening effect. XRD analysis results show that no other elemental reactions produce phases in the prepared component, indicating that other alloying elements such as Al and Si are dissolved in the matrix, and no chemical reactions occur between the elements added to the matrix alloy to generate impurities.
[0097] Microhardness, friction and wear and corrosion resistance measurement
[0098] from Figure 7 As can be seen from the Vickers hardness chart, the hardness of the component prepared by the present invention is significantly improved compared with the matrix material, and the hardness increases with the increase of the amount of nanodiamond added. The component prepared by the present invention has better mechanical properties, and the uniformly distributed network structure can effectively improve the mechanical properties of the material.
[0099] In addition, from Figure 8 It can be seen that the self-corrosion potential and breakdown potential of TC11-based composite materials with ND added up to 1.5 wt.% are higher than those of commercial Stellite 6.
[0100] Figure 9 Tribological tests on different samples showed that the composite material of the present invention has a lower average coefficient of friction than the original TC11 and Stellie 6 alloys. This indicates that the addition of ND increases the lubrication of the alloy surface. Combined with the microhardness test results, it can be seen that the composite material of the present invention has better wear resistance.
[0101] However, since the components in Comparative Examples 1 and 2 do not simultaneously possess a three-dimensional network structure and TiC-ND within the network structure, their wear resistance and corrosion resistance cannot be improved in a dual manner.
[0102] Therefore, the components prepared by the method of the present invention achieve a dual improvement in wear resistance and corrosion resistance.
[0103] While the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the invention. Those skilled in the art can make various modifications and refinements without departing from the spirit and scope of the invention. Therefore, the scope of protection of the present invention shall be determined by the claims.
Claims
1. A method for preparing a corrosion-resistant and wear-resistant protective patch for steam turbine blades, characterized in that, Includes the following steps: S1. Weigh the dried nano-diamond powder and titanium alloy pre-alloyed powder according to the required mass percentage, and mix and ball-mill until the nano-diamond powder is uniformly attached to the surface of the titanium alloy pre-alloyed powder to obtain mixed powder. S2. The mixed powder obtained in step S1 is sintered using hot isostatic pressing (HIP) sintering process, which allows nanodiamond (ND) to enter the matrix grain boundaries and generate TiC layers in situ, forming a core-shell unit (TiC-ND) with nanodiamond (ND) as the core and TiC as the shell, thus obtaining a rough blank. S3. The rough blank obtained in step S2 is subjected to heat treatment to regulate the microstructure, so that a portion of TiC-ND is uniformly distributed at the grain boundaries of the matrix to form a three-dimensional network structure, while another portion of TiC-ND is dispersed within the three-dimensional network structure, thus obtaining the required protective patch.
2. The method for preparing the corrosion-resistant and wear-resistant protective patch for turbine blades according to claim 1, characterized in that, TiC-ND dispersed within the three-dimensional network structure accounts for 5% to 25% of the total TiC-ND volume.
3. The method for preparing the corrosion-resistant and wear-resistant protective patch for turbine blades according to claim 1, characterized in that, The size of the nanodiamond powder is 5 nm to 50 nm.
4. The method for preparing the corrosion-resistant and wear-resistant protective patch for turbine blades according to claim 1, characterized in that, The hot isostatic pressing sintering process includes: The mixed powder obtained in step S1 is loaded into a carbon steel sleeve for sealing and degassing, and then placed in a hot isostatic pressing furnace for sintering and heat preservation under vacuum conditions.
5. The method for preparing the corrosion-resistant and wear-resistant protective patch for turbine blades according to claim 4, characterized in that, The powder-filled packaging is then vacuum-treated at 500℃~600℃ to achieve a vacuum level of 1×10⁻⁶ inside the packaging. -4 pa~1×10 -3 pa.
6. The method for preparing the corrosion-resistant and wear-resistant protective patch for turbine blades according to claim 4, characterized in that, The process parameters for hot isostatic pressing (HIP) sintering include: pressure of 90 MPa to 150 MPa, sintering temperature of 850 ℃ to 920 ℃, and holding time of 4 h to 8 h.
7. The method for preparing the corrosion-resistant and wear-resistant protective patch for turbine blades according to claim 1, characterized in that, The process parameters for heat treatment microstructure control include: temperature 1020 ℃~1080 ℃, holding time 1 h~2 h, and air cooling.
8. The method for preparing the corrosion-resistant and wear-resistant protective patch for turbine blades according to claim 1, characterized in that, The mass ratio of nanodiamond powder to the mixed powder is 0.5% to 1.5%.
9. The method for preparing the corrosion-resistant and wear-resistant protective patch for turbine blades according to claim 1, characterized in that, The titanium alloy pre-alloyed powder is TC11, with an average particle size of 53 μm to 150 μm.
10. A turbine blade protective patch prepared by the method described in any one of claims 1-9.